2009
DOI: 10.1016/j.ydbio.2009.09.030
|View full text |Cite
|
Sign up to set email alerts
|

On the roles of Notch, Delta, kuzbanian, and inscuteable during the development of Drosophila embryonic neuroblast lineages

Abstract: The generation of cellular diversity in the nervous system involves the mechanism of asymmetric cell division. Besides an array of molecules, including the Par protein cassette, a heterotrimeric G protein signalling complex, Inscuteable plays a major role in controlling asymmetric cell division, which ultimately leads to differential activation of the Notch signalling pathway and correct specification of the two daughter cells. In this context, Notch is required to be active in one sibling and inactive in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…Alternatively, Insc is only strictly required in cells born early in the NB lineages hence later born DA neurons within the same clusters are not affected resulting in less than double the size of neurons in these clusters. Differential requirement for insc based on the birth order of cells in NB lineages has been demonstrated in some embryonic NB lineages [49]. Collectively, our data indicates a critical role of the ACD mechanism in fate specification of most DA neurons in Drosophila .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Alternatively, Insc is only strictly required in cells born early in the NB lineages hence later born DA neurons within the same clusters are not affected resulting in less than double the size of neurons in these clusters. Differential requirement for insc based on the birth order of cells in NB lineages has been demonstrated in some embryonic NB lineages [49]. Collectively, our data indicates a critical role of the ACD mechanism in fate specification of most DA neurons in Drosophila .…”
Section: Discussionsupporting
confidence: 51%
“…Notch has been described as an effector of asymmetric cell division and binary sibling cell fate resolution [11], [48], [49]. To investigate the role of Notch signaling in the specification of embryonic DA neurons, we first analyzed TH expression in the ventral midline of Notch 55e11 mutants and found supernumerary TH expressing cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when abdA is knocked down (l, wor4abdAi) Dl expression is largely confined to the NB (j′-l′) Dl expression with brightness adjusted to highlight this difference. (m, m′) The glia cells form a more elaborate network around the NBs in the abdominal neuromeres (green repo4mCD8GFP, red Dpn) of the developing CNS in flies and mammals, 27,28,[42][43][44] and is involved in the non-autonomous regulation of cell survival by hedgehog signaling in the developing eye. 29 We find that the N pathway is required for NB death in the embryo, in contrast to previous data showing that N is not involved in pNB death later in development.…”
Section: Discussionmentioning
confidence: 99%
“…The Notch signaling pathway plays a role in distinguishing the fates of these two postmitotic cells (fates A and B) (Udolph et al, 2009). To address the role of Notch in the specification of CCAP neurons we examined its expression in mutants of sanpodo (spdo), a gene required for asymmetric cell division (Babaoglan et al, 2009 We examined whether the number of CCAP neurons was altered in Df(3L)H99 embryos and found that an extra CCAP cell appeared in segments SE1-T2, whereas in T3 and the abdominal segments the number was not altered (Fig.…”
Section: Role Of Notch In Ccap Specificationmentioning
confidence: 99%